Motivation and perceived motivational climate by adolescents in face-to-face physical education during the COVID-19 pandemic - Mata, C.; Onofre, M.; Costa, J.; Ramos, M.; Marques, A.; Martins, J. (Sustainability, 2021)
The COVID-19 pandemic impacted adolescents’ lives, leading to unprecedented changes in their routines, especially in education. Face-to-face physical education (PE) classes during COVID-19 were affected in organization, possibly conditioning students’ participation, motivation and learning. Based on the achievement goal and self-determination theories, the aim of this study was to analyze and compare the motivational indicators of adolescents in face-to-face PE classes during COVID-19, according to gender, educational level and physical activity (PA). A total of 1369 students participated in the study (621 boys and 748 girls; mean age: 14.4 years; SD: 1.74). Data were collected via an online questionnaire and analyzed using MANCOVAs adjusted for age, pre- and post-COVID-19 PA, socioeconomic status and BMI (Z-score). Differences in achievement goals, motivational climate and motivational regulation levels were found in different groups by gender, PA and educational level, favoring older and more active participants. A more positive motivational profile was found for girls in general and, specifically, for active boys, regarding more self-determined motivations and mastery goal orientations. Overall, this study’s findings suggest that the restrictions related to face-to-face PE classes during the COVID-19 pandemic had a negative impact on students’ motivation.